The role of power relationships, trust and social networks in shaping milk quality in Kenya - Nyokabi, N.S.; Boer, I.J.M. de; Bijman, J.; Bebe, B.; Aguilar-Gallegos, N.; Phelan, L.; Lindahl, Johanna F.; Bett, Bernard K.; Oosting, S.J. (Informa UK Limited, 2023)
The objective of this study was to examine social networks in dairy value chains (DVCs) in Kenya and understand how DVC actors’ power relationships and trust influence their behaviour regarding milk quality. We conducted a stakeholder analysis using the Net-Map tool in Laikipia, Nakuru and Nyandarua counties in Kenya. VisuaLyzer software was used to analyse the social networks. Thematic content analysis of the discussions, recorded during the mapping exercise, was undertaken using ATLAS.ti. Formal DVC had more actors and dense social networks characterised by vertical and horizontal integration, high levels of power asymmetries between actors, limited trust and short-term contractual arrangements. Informal DVC was characterised by fewer actors and less dense social networks, low levels of power asymmetries between actors and a high level of trust due to the existence of reciprocal personal relationships. Milk was perceived to be of higher quality in the formal value chain reflecting top-down enforcement of milk standards, bottom-up collective action, power asymmetries and contractual relationships. Poor milk quality management in the informal DVC underscores the need for powerful actors, e.g. regulatory agencies, and buyers such as processors, to influence other DVC actors’ behavioural change. Understanding and leveraging DVC social networks and actors’ power and addressing power asymmetries and enhancing trust between actors will increase compliance with milk quality standards. There is an urgent imperative to design policies and interventions which empower DVC actors, by providing economic incentives, enhancing their skills and knowledge and their access to infrastructure which facilitates milk quality improvement.